2020
DOI: 10.1177/1747493020909545
|View full text |Cite
|
Sign up to set email alerts
|

Global Stroke Statistics 2019

Abstract: Background Data on stroke epidemiology and availability of hospital-based stroke services around the world are important for guiding policy decisions and healthcare planning. Aims To provide the most current incidence, mortality and case–fatality data on stroke and describe current availability of stroke units around the world by country. Methods We searched multiple databases (based on our existing search strategy) to identify new original manuscripts and review articles published between 1 June 2016 and 31 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
214
4
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(230 citation statements)
references
References 63 publications
3
214
4
9
Order By: Relevance
“…In order to assess a person's attitude to a possible stroke event, the following closed-ended question was asked: "If you think someone is having the symptoms of a stroke, which will be your first reaction?" The three options to choose from as a response to this question were as follows: (1) No specific action is required; (2) Treatment should be sought, although not necessarily immediately; and (3) This is an emergency and medical attention should be sought immediately; the correct one being the one which recognized the possibility of treatment and the importance of the time factor.…”
Section: Main Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess a person's attitude to a possible stroke event, the following closed-ended question was asked: "If you think someone is having the symptoms of a stroke, which will be your first reaction?" The three options to choose from as a response to this question were as follows: (1) No specific action is required; (2) Treatment should be sought, although not necessarily immediately; and (3) This is an emergency and medical attention should be sought immediately; the correct one being the one which recognized the possibility of treatment and the importance of the time factor.…”
Section: Main Outcomesmentioning
confidence: 99%
“…Strokes continue to be a global health issue and a social problem, a situation expected to worsen in the coming years as the population ages. Strokes represent one of the major causes of mortality, dependency, and long-term disability in adults, proving to be highly expensive for the patients, their families, the health services, and the community as a whole [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…α7nAChR is a crucial receptor mediating cholinergic anti-in ammatory pathway. The stimulation of α7nAChR inhibits the activation of NF-κB signaling in microglia, reduced M1 microglia in the peri-infarct brain regions, and reduced brain injury in permanent MCAO (pMCAO)mice [2] [25] . In this study, we found that α7nAChR protein expression signi cantly decreased in the ischemic penumbra regions in tMCAO rats, while it was restored by GSS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is characterized by high morbidity and disability rate, and is also one of the deadliest diseases globally [1]. Ischemic stroke occupy the vast majority of stroke caused by blockage of blood circulation to the brain, resulting in pathophysiologic events like excitatory amino acids toxicity, ion imbalances and oxidative stress, leading to accumulation of hypoxia and toxic substances such as in ammatory cytokines, as well as the death of brain cells, and may induce subsequent neurobehavioral de cits in stroke survivors.…”
Section: Introductionmentioning
confidence: 99%